2016
DOI: 10.1016/j.iswcr.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Nitrogen Index to assess nitrate leaching and water drainage from plastic-mulched horticultural cropping systems of Florida

Abstract: 2017-08-30T02:06:31

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Nitrogen loss through nitrate leaching from the root zone of agricultural lands has a negative impact on the groundwater quality (Marchi et al, 2016) and can reduce soil fertility, thus affecting crop yields (Jabloun et al, 2015). In general, grasslands have a large nitrogen uptake capacity and therefore show a low nitrate leaching risk (Cameron et al, 2013).…”
Section: Potential Nitrate Leachingmentioning
confidence: 99%
“…Nitrogen loss through nitrate leaching from the root zone of agricultural lands has a negative impact on the groundwater quality (Marchi et al, 2016) and can reduce soil fertility, thus affecting crop yields (Jabloun et al, 2015). In general, grasslands have a large nitrogen uptake capacity and therefore show a low nitrate leaching risk (Cameron et al, 2013).…”
Section: Potential Nitrate Leachingmentioning
confidence: 99%
“…This rate can be an average of 417 kg • ha -1 (Shukla et al, 2014) or higher (up to 470 kg • ha -1 ) (Cantliffe et al, 2009) for a single production season. Although N is considered to be the most limiting nutrient for most nonleguminous production systems, excessive applications of fertilizer and/or water could lead to nutrient losses from a cropping system (Marchi et al, 2016;Zotarelli et al, 2007). This is because N in the form of nitrate (NO 3 --N) has a high diffusivity rate in soil solution (Sato et al, 2009), resulting in high mobility in the soil, especially under saturated conditions.…”
mentioning
confidence: 99%
“…For example, researchers in China created an integrated model for assessment of fertilizer management and quantitatively rank the potential risk to the environment effectively. Also, researchers in the U.S. concluded that the use of cover crops potentially reduces N leaching (Lei et al, 2010;Marchi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%